Working conditions in the informal economy : a comparative study of the charcoal industry in Otjozondjupa Region and shebeens in Khomas Region - Namibia. - Nicodemus, Meriam (My University, 2011)
The aim of this study is to investigate the working conditions of workers in the informal economy. Specifically, this study investigated the workers in shebeens and the charcoal industry using both the Decent Work Deficit Index and the Global Value Chain analysis. The shebeen workers are linked to the Namibia Breweries via the Producer Driven Value Chain and the charcoal workers are linked to the buyers beyond the borders of Namibia via the Buyer Driven Value Chain. The research methods employed are qualitative and quantitative. Furthermore, the study investigated whether the workers are enjoying benefits such as paid leave days. An examination of the literature reveals that the workers at the bottom end of the value chain tend to have a low level of security. The working conditions of the workers are usually compromised by the profit maximisation nature of capitalism and non-compliance with labour laws, leading to social downgrading which result in poor working conditions. The Decent Work Deficit Index has seven variables namely: Labour Market Security; Employment Security; Job Security; Work Security; Skills Reproduction Security; Representation Security; and Income Security. The overall findings of the study is that the shebeen scored low security levels in six out of seven variables, while charcoal workers scored five low security level out of seven variables. The study further showed that labour inspection is absent in the shebeen and very low in the charcoal industry. The findings of the study suggest that effective implementation of labour laws together with collective voice of workers will improve the working conditions.